Die Frau im 19. Jahrhundert - Schlesinger-Eckstein, Therese (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1902)
Discussed in this study of the woman of the 19th century are the following topics: women in industry and trade, the middle-class woman, and marriage, prostitution and motherhood.